FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN ALAT KONTRASEPSI SUNTIK PADA AKSEPTOR KB DI PUKSESMAS DUONO - Magawe, Kartini; Retnaningsih, Reny; Alim, Zainal (NHM PRESS, 2024)
The Family Planning Program is an essential part of a country's development to increase the community's concern and role through the maturation of marriage age, birth control, family resilience development, and family welfare improvement to realize a happy and prosperous family. In Indonesia, the most widely used contraceptive method is the injection method, which is 47.96%. Birth control acceptors widely use injectable contraception because it is simple, safe, and effective. This study aims to determine the relationship between age, knowledge, and attitude with the use of injectable contraceptives in family planning acceptors at the Duono Health Center. This study is an analytical survey research with a cross-section study design. The sampling technique is the total population. The population in this study is all women of childbearing age who use contraceptives at the Duono Health Center. Data analysis uses the Chi-square test with a confidence level of 95% (α= 0.05). The results of the statistical test showed that the variables related to the use of injectable contraceptives were age (p-value = 0.000) and knowledge (p-value = 0.000). And the variable that is not related to the use of injectable contraceptives is attitude (p-value = 0.416).